"I just don't focus on my needs." The unmet health needs of partner and offspring caregivers of people with dementia: A qualitative study. (January 2018) - Tatangelo, Gemma; McCabe, Marita; Macleod, Ashley; You, Emily
Abstract: Background: Family caregivers of people with dementia have significant unmet health needs. There is a lack of research that differentiates between the needs that are specifically relevant to partner and offspring caregivers. Objective: The aim of this study was to examine the health needs of partner and offspring caregivers of older people with dementia, including the barriers they experience in meeting their needs. Method: Semi-structured interviews were conducted with 24 family caregivers of community-dwelling people with dementia. Of these, 12 were partner caregivers (4 men, 8 women) and 12 were offspring caregivers (2 men, 10 women). The interviews were transcribed and analysed using thematic analysis. Results: Five themes were identified within the data. The first theme represents caregivers' overall assessment and perception of their health needs. The remaining four themes represent the most important aspects of caregivers' health needs; mental health, emotional support and social relationships, healthy diet and exercise, and personal time. While these themes were similar for offspring and partner caregivers, the specific needs and barriers within these areas were different. A prominent barrier for partner caregivers was that they had difficulty in acknowledging their needs. Despite this, partner caregivers demonstrated unmet emotional support needs, as they no longer had emotional support from their partner with dementia. They also had an unmet need for time away from the care-giving role, yet they were reluctant to leave the person with dementia. Offspring caregivers' unmet health needs were easily identified and were focused on their unmet mental health needs and feeling socially isolated. These unmet mental health and social support needs were related to their unmet health needs in other areas such as exercise, diet and having time to themselves. Conclusion: Caregivers have significant unmet needs and these are often complex, multidimensional, and they often differ between partner and offspring caregivers. Gaining a more detailed understanding of the needs and barriers that are particularly relevant to either partner or offspring caregivers will assist in the development of interventions that are tailored to the unique needs of caregivers.